2022
DOI: 10.1038/s42004-022-00630-6
|View full text |Cite
|
Sign up to set email alerts
|

Open questions on bonding involving lanthanide atoms

Abstract: In-depth understanding of the bonding characteristics of the lanthanide ions in contemporary lanthanide-based materials is mandatory for tailoring their properties for novel applications. Here, the authors elaborate on open questions regarding the bonding situation in mainly molecular lanthanide (4f) compounds, where, as compared to their actinide (5f) analogs in which covalency of the bonds is a common feature, this is still under discussion for the 4f compounds.The bonding properties of the lanthanide 4f ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Recently, the covalency in the lanthanide bonding and the non-negligible contribution of 4f orbitals in the bonding have attracted more attention. Different from the traditional view of lanthanides mainly forming ionic bonds, advanced spectral measurements indicate that they also can engage in covalent bonding interactions. The covalency of bonds is enhanced by the large orbital overlap and small energy difference between the metal and ligand orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the covalency in the lanthanide bonding and the non-negligible contribution of 4f orbitals in the bonding have attracted more attention. Different from the traditional view of lanthanides mainly forming ionic bonds, advanced spectral measurements indicate that they also can engage in covalent bonding interactions. The covalency of bonds is enhanced by the large orbital overlap and small energy difference between the metal and ligand orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…The spin density is mainly shared by the three Er atoms with negligible contribution from the acetylide unit C 2 (Figure b). The well-examined Sc 3 C 2 @C 80 shows that the spin density is mainly localized on the C 2 unit, and its electronic structure is best described as (Sc 3 ) 9+ (C 2 ) 3– @C 80 . The α -SOMO of Er 3 C 2 @C 80 evidently exhibits the localization of a single electron between the three Er ions (Figure c), presenting Er–Er–Er bonding with the main composition of the s and p orbitals of Er (Figure S4 shows other canonical molecular orbitals of Er 3 C 2 @C 80 , and α -SOMO – 4 also has the Er–Er–Er bonding feature). Additionally, the color-filled contour plot of electron localization functions (ELFs) further confirms the localization of the single electron between Er ions (Figure S5a).…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical property of Er 3 C 2 @I h (7)-C 80 , however, astonishingly varies from that of Sc 3 C 2 @I h (7)-C 80 . Er 3 C 2 @ I h (7)-C 80 exhibits the reversible oxidation step and first reversible reduction step at +0.21 and −0.89 V, respectively, which are shifted in the anodic and cathodic directions by 390 and 240 mV, respectively, in comparison with that of Sc 3 C 2 @ I h (7)-C 80 (Table 1). This indicates a considerable difference of the frontier MO energies for these two molecules, which is highly associated with their electronic configurations and thus the bonding nature of the inner clusters discussed above.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…11 For example, La 3+ has an absolute chemical hardness of 15.4 eV, while that of Ac 3+ , the corresponding actinide, is 14.4 eV. 12 In a recent publication, Vitova et al 10 identified open questions in the current understanding of the covalent bonding of lanthanides such as the involvement of 5d electron orbitals and the nature of orbital overlap between lanthanide ions and the complexing ligand. 12 While the community lacks an orbital-level understanding of ligand-ion complexation of lanthanides, there are many studies that investigate the effect of ligand chemistry on the thermodynamics and kinetics of lanthanide-ion complexation.…”
Section: Introductionmentioning
confidence: 99%